The Roots of Banking Crises: The Macroeconomic Context - Michael Gavin; Ricardo Hausmann (Inter-American Development Bank, Office of the Chief Economist, 1996)
This paper discusses the ways in which macroeconomic developments can put stress on banks, and in extreme cases lead to banking crises. These macroeconomic causes of bank vulnerability and crisis have important implications for regulatory regimes, and for macroeconomic policy itself. Much of the discussion emphasizes the need for monetary policy to be set with an eye on the state of the domestic banking system as an occasionally important consideration. One purpose of this paper is to promote a discussion of how to do a better job of incorporating weak banking systems into macroeconomic policy management.
Keywords: 330